Timed Ang2-targeted therapy identifies the Angiopoietin-tie pathway as key regulator of fatal lymphogenous metastasis - Gengenbacher, Nicolas; Singhal, Mahak; Mogler, Carolin; Hai, Ling; Milde, Laura; Abdul Pari, Ashik Ahmed; Besemfelder, Eva; Fricke, Claudine; Baumann, Daniel; Gehrs, Stephanie; Utikal, Jochen; Felcht, Moritz; et al. (Cancer discovery, 2021)
Recent clinical and preclinical advances have highlighted the existence of a previously hypothesized lymphogenous route of metastasis. However, due to a lack of suitable preclinical modeling tools, its contribution to long-term disease outcome and relevance for therapy remain controversial. Here, we established a genetically engineered mouse model (GEMM) fragment-based tumor model uniquely sustaining a functional network of intratumoral lymphatics that facilitates seeding of fatal peripheral metastases. Multiregimen survival studies and correlative patient data identified primary tumor-derived Angiopoietin-2 (Ang2) as a potent therapeutic target to restrict lymphogenous tumor cell dissemination. Mechanistically, tumor-associated lymphatic endothelial cells (EC), in contrast to blood vascular EC, were found to be critically addicted to the Angiopoietin-Tie pathway. Genetic manipulation experiments in combination with single-cell mapping revealed agonistically acting Ang2-Tie2 signaling as key regulator of lymphatic maintenance. Correspondingly, acute presurgical Ang2 neutralization was sufficient to prolong survival by regressing established intratumoral lymphatics, hence identifying a therapeutic regimen that warrants further clinical evaluation. - Significance: Exploiting multiple mouse tumor models including a unique GEMM-derived allograft system in combination with preclinical therapy designs closely matching the human situation, this study provides fundamental insight into the biology of tumor-associated lymphatic EC and defines an innovative presurgical therapeutic window of migrastatic Ang2 neutralization to restrict lymphogenous metastasis.This article is highlighted in the In This Issue feature, p. 211
Gesehen am 03.05.2021
Published online first October 26, 2020